Consequences of introducing geometric GTV to CTV margin expansion in DAHANCA contouring guidelines for head and neck radiotherapy. Issue 1 (January 2018) - Hansen, Christian Rønn; Johansen, Jørgen; Samsøe, Eva; Andersen, Elo; Petersen, Jørgen B.B.; Jensen, Kenneth; Andersen, Lisbeth J.; Sand, Hella M.B.; Bertelsen, Anders S.; Grau, Cai
Abstract: Background and purpose: Defining margins around the Gross Tumour Volume (GTV) to create a Clinical Target Volume (CTV) for head and neck cancer radiotherapy has traditionally been based on presumed knowledge of anatomical routes of spread. However, using a concentric geometric expansion around the GTV may be more reproducible. The purpose of this study was to analyse the inter-observer consistency of geometric CTV delineation with adaptation for anatomical boundaries versus anatomically defined CTVs. Material and methods: Radiation oncologists at four Danish cancer centres delineated high, intermediate and elective dose CTVs (CTV1, CTV2 and CTV3, respectively) in a patient-case template (stage IV squamous cell carcinoma of the oropharynx), first using mainly anatomical margins (original standard) and then using concentric geometric expansion (new standard). Each centre made a dummy-run radiotherapy plan based on the delineated CTVs. The difference between the CTV contours and the radiotherapy plans was evaluated across the centres. Results: Anatomy-based contours were significantly more heterogenous and showed larger volume differences between centres than geometric margins. Dice similarity coefficient increased by 0.29 and mean surface distance decreased by 4 mm for CTV1. Use of consistent CTV volumes resulted in more consistent irradiated volumes between centres. Conclusion: Introduction of geometric margins resulted in more uniform CTV1 and CTV2 delineation. Geometric CTV expansion was easier, left less room for misinterpretation, and resulted in more uniform treatment plans with similar irradiated high and intermediate dose volumes across all centres.